Adhesion between ethylene‐propylene‐diene monomer and thermoplastics in two‐component injection molding: Effect of dicumylperoxide as curing agent. Issue 41 (23rd March 2020) - Laing, Brittany; De Keyzer, Jozefien; Seveno, David; Van Bael, Albert
Abstract: Strong adhesion at the interface is an important aspect in two‐component (2K) injection molding. It was therefore investigated whether dicumylperoxide (DCP) as curing agent in ethylene‐propylene‐diene monomer (EPDM) could stimulate interdiffusion and/or induce chemical bonding with thermoplastics. EPDM mixtures containing DCP concentrations between 2 to 8 parts per hundred rubber (phr) were combined with polar and non‐polar thermoplastics. Changes in EPDM physico‐mechanical bulk properties were analyzed, and the adhesion was evaluated by high temperature contact angle measurements and tensile testing. Results showed that DCP concentration did not influence EPDM‐thermoplastic compatibility. However, EPDM adhesion with polyethylene (PE) did improve when using up to 6 phr DCP (57% adhesion) as crosslinking is promoted. While with polypropylene (PP), adhesion linearly decreased (from 55% to 35% adhesion) with higher DCP concentrations due to prevailing scission reactions. Adhesion through chemical bonding with acrylonitrile‐butadiene‐styrene (ABS) caused better adhesion at 4 phr (43% adhesion) compared to polycarbonate (PC) at 4 phr (13% adhesion) where only limited interdiffusion occurs. Thus, selecting the optimal DCP concentration is highly important to boost adhesion between EPDM and thermoplastics. Furthermore, at these optimal DCP concentrations, physico‐mechanical properties require consideration as these properties were significantly affected. Abstract :